PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBASIS BERDEFERENSIASI DALAM MATA PELAJARAN IPS MATERI KERAGAMAN BUDAYA DISEKOLAH SDN KERTAJAYA SURABAYA - Safitri, Brigta Yovina; Rarasaning Satianingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the Problem Based Learning (PBL) model with differentiation in Social Studies (IPS) focusing on cultural diversity material in Grade IV at SDN Kertajaya Surabaya. The research focuses on teacher activities in designing and conducting learning, student activities during the learning process, and teacher and student responses to the application of differentiated PBL. The research employed a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The findings indicate that differentiated PBL enhances student engagement, fosters respect for cultural diversity, and strengthens understanding of social values in daily life. Teachers act as facilitators who adjust differentiation strategies based on students’ readiness, interests, and learning profiles. Students actively engage cognitively, affectively, psychomotorically, and collaboratively through group discussions, creative products, and presentations. Thus, the integration of PBL and differentiation is an effective approach to support the implementation of the Merdeka Curriculum, while equipping students with 21st-century skills such as communication, collaboration, creativity, and empathy.